2023
DOI: 10.1101/2023.02.17.528066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The timing of transcription of RpoS-dependent genes varies across multiple stresses inEscherichia coliK-12

Abstract: The alternative sigma factor RpoS regulates transcription of over 1000 genes in Escherichia coli in response to many different stresses. RpoS levels rise continuously after exposure to stress, and the consequences of changing levels of RpoS for the temporal patterns of expression of RpoS-regulated genes has not been described. We measured RpoS levels at various times during the entry to stationary phase, or in response to high osmolarity or low temperature, and found that the time required to reach maximum lev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This implies that while RpoS regulates many genes in the cold, it is only a fraction of the genes that are cold- regulated overall. Reassuringly, of the 232 DE genes in E. coli in this study, 189 (81%) were previously identified as RpoS-regulated at 15°C by Adams et al (39). In S. enterica, 189 genes are DE between wt and Δ rpoS strain, 80% of the number of genes that are RpoS-regulated in E. coli.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…This implies that while RpoS regulates many genes in the cold, it is only a fraction of the genes that are cold- regulated overall. Reassuringly, of the 232 DE genes in E. coli in this study, 189 (81%) were previously identified as RpoS-regulated at 15°C by Adams et al (39). In S. enterica, 189 genes are DE between wt and Δ rpoS strain, 80% of the number of genes that are RpoS-regulated in E. coli.…”
Section: Resultssupporting
confidence: 56%
“…The alternative sigma factor RpoS is known to be activated at low temperature in E. coli where it regulates the expression of several hundred genes (39). We compared the role of RpoS in E. coli and its close relative S. enterica during growth at 15°C.…”
Section: Rpos Regulation Of the Response To Temperature Shiftmentioning
confidence: 99%
“…Different stressed environments activate σ S in various ways, thereby influencing the levels of σ S and affecting certain promoters [29,31,54]. For instance, only 156 of the 1663 genes tested and their promoters can be activated in all of the stressed conditions tested (stationary phase, high osmolarity, and low temperature) were reported in a previous study [29].…”
Section: Dynamics Under Different Fermentation Patternsmentioning
confidence: 83%
“…Different stressed environments activate σ S in various ways, thereby influencing the levels of σ S and affecting certain promoters [29,31,54]. For instance, only 156 of the 1663 genes tested and their promoters can be activated in all of the stressed conditions tested (stationary phase, high osmolarity, and low temperature) were reported in a previous study [29]. In the ideal fermentation model, the logarithmic phase is typically characterized by an abundance of nutrients, while the stationary phase is marked by high osmotic pressure and starvation.…”
Section: Dynamics Under Different Fermentation Patternsmentioning
confidence: 99%
See 1 more Smart Citation